Effect of psychosocial safety climate on work-family conflict and psychological health among working couples - Muhamad Nasharudin, Nurfazreen Aina; Rui, Zhao (Korean Society of Occupational and Environmental Medicine, 2024)
Background: The purpose of the study was to look into how work-family conflict (WFC), family-work conflict (FWC), and psychological health are affected by the psychosocial safety climate (PSC). First, the study suggested that for both husband and wife, PSC moderates the relationship between job demands and WFC. Second, the study predicted FWC mediates the relationship between WFC and depressive symptoms through the "crossover"process. Methods: The study design used a multi-source sample that involved 350 teachers and their working spouses (n = 700). The analysis of mediation and moderation among job demands, WFC, FWC, PSC, and depressive symptoms was conducted using SPSS and structural equation modeling AMOS software. Results: For the teacher's sample, based on behavioral (β = 0.166, p < 0.05) and strain-based (β = 0.170, p < 0.05) aspects, the hierarchical regression analysis revealed that the PSC moderates the relationship between physical demand and WFC. The results also showed that the relationship between time-based WFC and emotional demand is moderated by PSC (β = 0.103, p < 0.05). Next, the analysis found that PSC moderates the association between cognitive demand and WFC of strain-based (β = 0.179, p < 0.05). For the spouse's sample, according to the analysis, PSC moderates the relationship between strain-based WFC and physical demand (β = 0.091, p < 0.05). The study also revealed that FWC serves as a mediator in the relationship between WFC and depressive symptoms in both husbands (β = 0.233, p < 0.01) and wives (β = 0.135, p < 0.001). Conclusions: Overall, this study contributes significant insights to the current literature by examining the impact of PSC on the psychological well-being of individuals and others through the crossover process.